Effect of a Compassion-Focused Training Program in Palliative Care Education for Medical Students. (March 2013) - Shih, Chih-Yuan; Hu, Wen-Yu; Lee, Long-Teng; Yao, Chien-An; Chen, Ching-Yu; Chiu, Tai-Yuan
Background: Compassion is the key value of humanities perspective. Little is known, however, concerning the impact of enhancing compassion on ethical decision making in end-of-life care. Methods: A total of 251 preclinical medical students were enrolled in a palliative care training course. A structured self-report questionnaire was administered before and after training. Results: Experience with caring for patients with terminal cancer was positively related to improvement in the decision of "truth telling is helpful to a good death." In addition, improvement in the perception of "compassionate care" was correlated with higher improvement in the decision of "discharge planning and home care." Conclusion: Compassion-focused training program can be helpful to improve medical students' competence in making more appropriate ethical decisions in end-of-life care.